Estimation of ginger bioactive compound solubilities in hot compressed water and enhancement with entrainer - Syed Jaapar, Syaripah Zaimah (Elsevier, 2015)
Knowledge concerning the solubility of ginger bioactive compounds in hot compressed water (HCW) is important for designing an extraction process with water as a green solvent. The solubilities of 6-gingerol and 6-shogaol in hot compressed water are calculated using the conductor-like screening model for real solvent (COSMO-RS) method to study the potential of water as a solvent. The comparison indicates that the calculated solubility is at a higher concentration for the binary system of 6-gingerol. +. water and 6-shogaol. +. water when compared to the HCW extraction. This illustrates the performance of the HCW extraction, which has not reached the equilibrium condition, and gives an opportunity to explore the options for further improving the process. The availability as well as the thermo-labile nature of the bioactive compounds are factors that must be considered for the improvement of HCW as a solvent. The solubilities of 6-gingerol and 6-shogaol in aqueous ethanol solutions are also calculated by the COSMO-RS method to study the entrainer effect of ethanol. The calculations with ethanol as entrainer indicate that the molecular cavity and contact interaction are changed so as to increase the solubilities. Based on the calculations, the suitable amount of ethanol as an entrainer is estimated to be 0.02. mole fraction for both 6-gingerol and 6-shogaol with an improved solubility of 1.86 and 1.76 times, respectively. In general, the addition of the entrainer will improve the recovery and operating parameters at a milder operating condition. This approach may be applied to other bioactives and will further strengthen the use of water as a solvent in natural extracts